"Language policy and the status of Yoruba in private primary schools in Abeokuta north local government area " (2010)
"The importance of mother tongue as a medium of instruction at the primary level of education is a subject of concern to language educators. While many studies have been carried out on public primary schools, not many have been done in private schools, hence the challenge to probe into problems facing the teaching of the mother tongue in this sector. Two hundred and fifty pupils and ten Yoruba teachers were randomly selected from five private primary schools in Ogun State. Three instruments used to obtain data were Pupil Questionnaire on Yoruba (PQY), Teacher Questionnaire on Yoruba (TQY) and an interview guide for head teachers. Data collected were analysed using simple percentages. The results showed that all the private schools used for the study did not encourage the use of Yoruba as a medium of instruction hence qualified Yoruba teachers were not recruited; teaching aids were not adequately provided; most teachers(80%) did not give assignments in Yoruba to their students and it was forbidden to speak Yoruba in schools(100%). Ironically, majority of the pupils spoke Yoruba at home and watched Yoruba programmes on television. The paper recommends that schools should encourage the use of Yoruba as a medium of instruction in early primary education while enough time should be allotted to it on the school timetable "